Real Writing with answers. - Palmer, Graham (Cambridge University Press, 2008)
A four-level skills series for adults and young adults. Learners can develop the skills they need to write English confidently wherever they are - at home, at work, travelling, studying or just in social situations with English-speaking friends. This edition comes with answers and audio CD